A PARAMETRIC ANALYSIS OF MEASURES 0-51 OF PITHOPRAKTA BY IANNIS XENAKIS - Cao, Shupeng (East Carolina University)
This Master's Thesis in Music Composition comes in two parts. The first part is a thesis discussing the analysis of Iannis Xenakis's Pithoprakta. The thesis includes three chapters. The first chapter provides background information about Xenakis and Pithoprakta. The second chapter discusses important scholarship about the piece and the methodology for my analysis. The final chapter is my original analysis focusing on measures 0-51 of Pithoprakta. The second part of this Master's Thesis contains my composition recital program and the score of my original composition for large ensemble which was to be premiered on April 4, 2020.
Keywords: Xenakis, Iannis, 1922-2001. Pithoprakta; Composition (Music)--Instruction and study